Necessary and Sufficient Conditions for Purchasing Halal Skincare: Extending the Theory of Planned Behavior - Khoirunnisa, Annes Nisrina; Ohgata, Satomi; Khoirunisa, Kharisa Rachmi; Pambekti, Galuh Tri; Yusfiarto, Rizaldi (Indonesian Journal of Halal Research, 2025)
This study aims to comprehensively analyze the factors influencing the purchasing intentions and attitudes of Indonesian Muslim youth toward halal skincare products. Utilizing the Theory of Planned Behavior (TPB), it integrates both external and internal components, including halal certification, halal literacy, and religiosity. Data were gathered from 233 Muslim adolescents, and the proposed model was evaluated using partial least squares structural equation modeling (PLS-SEM) to analyze net effect factors, followed by necessary condition analysis (NCA) to identify critical components. The outer loading values of PLS-SEM range from 0.736 to 0.945, indicating that the indicators used have a strong and reliable contribution to the constructs they represent. The research results indicate that the net effect analysis demonstrates that the dimensions of TPB and halal literacy significantly influence the purchase intention of halal skincare products. The NCA results indicate that Attitude (9.4%) and Perceived Behavioral Control (65.3%) play a crucial role in influencing consumers' purchase decisions for halal skincare products, with PBC being the most significant determinant. Halal Certification (16.5%-25.6%) serves as a key prerequisite for fostering a positive attitude, while Subjective Norms (5.8%-45.5%) become more influential once a fully established positive attitude is achieved.